THEONYMS, BIBLICAL NAMES, NAMES AND OTHER RELATED ONYMS MOTIVATED BY CHRISTIAN (CALENDAR) NAMES IN RADOMIR ANDRIĆ’S POETRY (Heritage, 2021)
This paper deals with theonyms and also with other similar names that are motivated by onyms and appellative lexis of the Christian origin and which are part of the wider study concerned with names as recorded in Radomir Andrić’s poetry. Semantical analysis and classification of theonyms, biblical names, Christian holy days, church names, icons, frescoes and other chrematonyms, personal names and nicknames of the holy men and of other similar onyms. The paper is followed by dictionary which is consisted of authentic, real names and unauthentic, unreal names of different types and kinds.
Keywords: Radomir Andrić, vocabulary, theonymy, calendar names, semantics, classification.